2018
DOI: 10.1177/1461348418756019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of posture and vibration magnitude on seat to head transmissibility during exposure to fore-and-aft vibration

Abstract: An experimental study has been conducted on the vibration simulator, developed as a mockup of a railway vehicle. In this paper, the effect of variations in the posture and vibration magnitude on head motions in three translational directions (fore-and-aft, lateral and vertical) are studied with seat vibration in fore-and-aft direction. Thirty healthy male subjects are exposed to random vibration with three vibration magnitudes of 0.4, 0.8 and 1.2 m/s 2 r.m.s. over the frequency range 1-20 Hz. The data results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…A reduced perturbation signal magnitude resulted in increase main response peak gains in all perturbation directions for head and trunk, accompanied with higher peak frequencies (Table 1a). Previous studies found similar non-linear effects of seat vibration magnitude (Bhiwapurkar et al, 2016;Bhiwapurkar, Saran and Harsha, 2019;Nawayseh and Griffin, 2003). These findings were explained by non-linear muscle yielding in response to increasing motion magnitudes (Nawayseh and Griffin, 2003;Matsumoto and Griffin, 2002).…”
Section: Discussionsupporting
confidence: 64%
“…A reduced perturbation signal magnitude resulted in increase main response peak gains in all perturbation directions for head and trunk, accompanied with higher peak frequencies (Table 1a). Previous studies found similar non-linear effects of seat vibration magnitude (Bhiwapurkar et al, 2016;Bhiwapurkar, Saran and Harsha, 2019;Nawayseh and Griffin, 2003). These findings were explained by non-linear muscle yielding in response to increasing motion magnitudes (Nawayseh and Griffin, 2003;Matsumoto and Griffin, 2002).…”
Section: Discussionsupporting
confidence: 64%
“…The term posture in the WBV literature is used loosely [8], where it can mean changes in pelvic rotation/tilt [19,20], tension in the spine [10], use of a backrest support [21,22], use of armrests [18,23], slouching [24], flexed and extended trunk and hip positions [25], and rotated trunk and neck positions [12,17,18,26,27]. In a study using nine different pelvis and spine postures, there were peaks in apparent mass at 5 and 10 Hz and peaks in seat-to-pelvis pitch transmissibility at 12 Hz [20].…”
Section: Introductionmentioning
confidence: 99%
“…The STHT has been measured in laboratory experiments simulating WBV exposure from a dozer machine [23] and railway vehicle [21]. In the dozer study, two sitting postures were used: one with the subject sitting in a standard posture supported by the seat back, and the second in a forward back-unsupported posture, where the arms were on their laps and their feet on a foot pedal while using the armrests or grasping the steering wheel [23].…”
Section: Introductionmentioning
confidence: 99%
“…Three biodynamic response functions were usually used to analyze the vibration characteristics of human body -seat to head transmissibility (STHT), apparent mass (AM), and mechanical impedance (MI) respectively. [7][8][9][10][11][12] In order to analyze the vibration of human body and improve ride comfort of vehicle, various models have been built to describe the vibration response characteristics of human body. [13][14][15][16] Lumped parameter model is a typical, simple method to analyses vibration responses of seated human body.…”
Section: Introductionmentioning
confidence: 99%